GeoGebra: Its Effects on Education Students Attitudes, Motivation, and Performance in College Algebra - Etcuban, Jonathan Olores; Leonard, Leonard (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2025)
Mobile applications like GeoGebra are crucial for learning algebraic function graphing among college students. This application provides interactive visual aids that improve comprehension and memory of complex ideas relating to graphing of algebraic functions. It aimed to determine the effects of GeoGebra software in smartphones on education students' attitudes, motivation, and performance in College Algebra at a technological state university in Cebu City, Philippines. The participants were 80 students [40 students in the control group and 40 in the experimental group] who were chosen using purposive sampling. The quasi-experimental method used three questionnaires (Fennema-Sherman Mathematics Attitude Scales, Mathematics Motivation Questionnaire, and Students' Algebra Performance). The data were treated using frequency, mean, standard deviation, Pearson r, and paired t-test. The study revealed that students' attitudes and motivations toward algebra do not have significant relationships with their pretest and posttest performances in graphing algebraic functions. However, there is a substantial difference between the students' posttest means scores in Algebra of the control and experimental groups. The study concluded that students' attitudes toward algebra improved when using GeoGebra software to learn graphing of algebraic functions. The researcher recommends integrating GeoGebra software into Algebra's curriculum to enhance students' performance in graphing algebraic functions.